Da'wah Methods for Coaching Prisoners in Correctional Institutions - Syafitri, Siska; Diana, Putri; Efendi, Efendi; Irayanti, Irma; Rahmanda, Rega (Suluah Pasaman, 2024)
People's diverse ways of thinking in dealing with developments in the times often trigger actions beyond their limits, especially when their desires are not in line with their sense of faith. In this context, correctional institutions play an important role as a place to develop prisoners through da'wah guidance, which aims to direct them back to the right path. This research aims to determine the effectiveness of the da'wah method in developing prisoners in Class II B Correctional Institutions. This research uses a qualitative method with a case study approach. Data sources were taken through in-depth individual and group interviews with five informants consisting of ustadz, prison officers, and prisoners. All data was analyzed thematically using model analysis interactive Miles & Huberman's. The results of this research show that; the effectiveness of the da’wah method in coaching prisoners in the Class II B Correctional Institution applied by the preacher is the lecture method with a technique at the beginning of the lecture inviting prisoners to read Asmaul Husna and self-introspection. This method is following Q.S An-Nahl verse 125, namely the mau'izah hasanah method. However, the success of this da’wah method is still not optimal, this can be seen from the results of observations and interviews that researchers have conveyed.